Serviços ecossistêmicos oferecidos por espaços verdes públicos e suas contribuições para a agenda 2030: subprefeitura da Mooca, SP, São Paulo, SP - Santos, Silvia Rosana dos (Universidade Federal de São Carlos, 2022)
Urban green spaces are places that contribute to the achievement of goals of the Sustainable Development Goals (SDGs) of the UN 2030 Agenda. These spaces are environments that can increase the supply of Ecosystemic Services (ES), which are essential to promote human well-being and a healthy terrestrial environment. The objective of this work was to evaluate the ESs offered by two (2) public green spaces located in the District Council of Mooca, East Zone of São Paulo’s city: the Alfredo Di Cunto Square, also known as Coletivo Horta das Flores and Visconde de Souza Fontes Square. The choice of these two squares is due to a low Index of Green Areas per inhabitant (2 to 5 m²/inhabitant) in Mooca District. To evaluate the ES provided by this green area, it was used the methodology proposed by Gaudereto et al. (2019), named Index of Ecosystemic Services for Green Areas (ISEAV). Among the results, the SE of regulation stands out, represented by the green cover, permeable area, canopy and burlap; which contributes to achieve the goals of SDG 6, SDG 13 and SDG 15. The supporting SE represented by vegetation covering, plant habits, species richness and its origin, native or exotic, contributes to the achievement of the SDG 15 and the SE of provision (SDG 2), since that, in the area, there is a vegetable garden with food plants, including non-conventional ones. The two green areas studied, Alfredo Di Cunto Square, also called Coletivo Horta das Flores and Visconde de Souza Fontes Square, contribute to the offer of many ESs that favor life quality for visitors, as well as to a more sustainable city and community (SDG 11) as it is a safe and inclusive green space.
Ecosystemic services offered by públic green spaces and its contribution for the un 2030 agenda: District council of Mooca, SP
Keywords: Serviços Ecossistêmicos; Áreas Verdes Urbanas; Objetivo do Desenvolvimento Sustentável; Ecosystemic Services; Sustainable Development Goal; Urban Green Areas; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL